Feasibility of Multi-component Seismic for Mineral Exploration - Ahmadi, Pouya (Curtin University, 2018)
Mineral industry uses potential-field methods to explore shallow-seated resources. As deposits are getting deeper, alternative technologies are needed. Seismic reflection is the only surface method reaching the desired depth. Utilising full-vector field may provide valuable information including better rock characterisation in term of composition, alternations and geotechnical properties for exploration. This research is hoped to add new knowledge along this path and inspire further multicomponent seismic studies in the mineral sector.